Effects of thermal stratification on the concentration of iron and manganese in a Tropical Water Supply Reservoir - Noor Halini Baharim,; Razali Ismail,; Mohamad Hanif Omar, (Universiti Kebangsaan Malaysia, 2011)
Thermal stratification in lakes is an important natural process that can have a significant effect on the water resource quality. The potential changes in chemical contents in water resulting from stratification are the production of ammonia, sulphides and algal nutrients and the increasing concentrations of iron and manganese. One of the water supply reservoirs located in Johor, Malaysia facing with high iron and manganese concentrations associated with the period of stratifications. This study showed that the level of thermal stratification in the reservoir varied at different time of the year. During the strongest period of stratification, the dissolved oxygen content was found to diminish significantly with depth and iron and manganese were recorded at the highest concentrations. Although significant period of rainfalls contributed to the natural destratification of reservoir, lower concentrations of iron and manganese only remained for a shorter period before the concentrations continued to increase with the onset of the thermal stratification. A good understanding on the behaviour of the reservoir may help to identify several measures for the improvement of water quality